Analysing Vehicular Congestion Scenario in Kuala Lumpur Using Open Traffic - Muhammad Ali; Saargunawathy Manogaran; Kamaludin Mohamad Yusof; Muhammad Ramdhan Muhammad Suhaili (Institute of Advanced Engineering and Science, 2018)
Traffic congestion on the roads is mainly the result of overcrowding and this phenomenon happens when a great number of vehicles storm the road, resulting in the disruption of the smooth traffic flow. This greatly affects the daily routines of the people. Not to mention the time that is wasted while a person feels stranded in such situation and it results in the loss of productivity, also deteriorates the societal behavior to a certain extent and have adverse effects on the economy. The natural calamities add to the miseries. It becomes very difficult to manage the traffic flow in situations when there are flash floods or other accidents. Therefore the trend of the traffic seems very unpredictable. The real-time information and the past data are deemed as the significant inputs for the predictive analysis. Modern day researchers perform the predictive analysis using the simulations as it does not seems to have any accurate and exact predictive model, mainly because of the higher complexity and the perplexing situation the researchers face while performing the analysis. Open Traffic seems to be a viable option, as it is an open source and can be linked with the Open Street. This research targets to study and understand the Open Traffic platform. In this regard the real-time traffic flow pattern in Kuala Lumpur area was successfully been extracted and the analysis was performed using Open Traffic. It was observed and deduced from the results that Kuala Lumpur faces congestion on every major avenue, junction or intersection it mostly owes to the offices and the economic and commercial centers during the peak hours. Some avenues experience the congestion problem due to the tourism.